The Impact of Structural Position Changes on Employee Performance and Organizational Effectiveness - Fauzan Hakim; Eneng Wiliana; Hengki Nurhuda (Lembaga Publikasi Ilmiah Nusantara, 2026)
Structural position changes have become an increasingly important human resource management strategy for higher education institutions undergoing organizational transformation. However, empirical evidence explaining how structural position changes simultaneously influence employee performance, organizational commitment, and organizational effectiveness remains limited, particularly within Indonesian Islamic higher education institutions. This study aims to examine the direct and indirect effects of Structural Position Changes (SPC) on Organizational Effectiveness through Employee Performance and Organizational Commitment. A quantitative cross-sectional design was employed using survey data collected from 185 academic and non-academic staff at Universitas Muhammadiyah Tangerang. The proposed model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings indicate that Structural Position Changes significantly improve Employee Performance (β = 0.412, p < 0.001), Organizational Commitment (β = 0.367, p < 0.001), and Organizational Effectiveness (β = 0.389, p < 0.001). Furthermore, Employee Performance and Organizational Commitment partially mediate the relationship between Structural Position Changes and Organizational Effectiveness. This study contributes to the human resource management literature by proposing an integrated mediation model that combines behavioral and attitudinal mechanisms to explain how structural changes enhance organizational effectiveness within Indonesian Islamic higher education institutions. The findings also have practical implications for university leaders seeking to design competency-based structural transformation strategies that improve institutional performance and strengthen employee commitment.